Long-Term Consequences of Adaptive Fetal Programming in Ruminant Livestock - Vautier, Allison N.; Cadaret, Caitlin N. (Frontiers in Animal Science, 2022)
Environmental perturbations during gestation can alter fetal development and postnatal animal performance. In humans, intrauterine growth restriction (IUGR) resulting from adaptive fetal programming is known as a leading cause of perinatal morbidity and mortality and predisposes offspring to metabolic disease, however, the prevalence and impact in livestock is not characterized as well. Multiple animal models have been developed as a proxy to determine mechanistic changes that underlie the postnatal phenotype resulting from these programming events in humans but have not been utilized as robustly in livestock. While the overall consequences are similar between models, the severity of the conditions appear to be dependent on type, timing, and duration of insult, indicating that some environmental insults are of more relevance to livestock production than others. Thus far, maternofetal stress during gestation has been shown to cause increased death loss, low birth weight, inefficient growth, and aberrant metabolism. A breadth of this data comes from the fetal ruminant collected near term or shortly thereafter, with fewer studies following these animals past weaning. Consequently, even less is known about how adaptive fetal programming impacts subsequent progeny. In this review, we summarize the current knowledge of the postnatal phenotype of livestock resulting from different models of fetal programming, with a focus on growth, metabolism, and reproductive efficiency. We further describe what is currently known about generational impacts of fetal programming in production systems, along with gaps and future directions to consider.